Designing a Bandung Perfume Shop Sales Information System Using Python - Amanda, Ryan; Kurnia, Dona; Akmal, Akmal (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Bandung Perfume Shop is a company that sells perfume. Based on observations, it was discovered that the Bandung Perfume Shop Information System activities maintain use the traditional way. Sales data collecting or recording operations continue to rely on paper media, specifically notebooks, which are prone to loss and damage, implying that the document preparation system is inadequate. Similarly, everything is done conventionally when it comes to data recapitulation and providing information or reports. Given this occurrence and all of its flaws, particularly low work efficiency, an information system that can replace the prior way is required in order to create efficient work. Information System Design as a solution to the above phenomenon at the Bandung Perfume Shop using the Python application (Object Oriented Programming Language), starting from March 2023. The research aims to provide an information system that can simplify and accelerate employee work processes in processing sales data at the Bandung Perfume Shop. The results of this study were collected in the form of an output Information System from the Python program that was created in outline by automating the old (traditional) system to the new system. The results of this study are projected to have a substantial impact on the sales and recapitulation processes in the future, improving work efficiency at the Bandung Perfume Shop.